GU Evaluation and Management of Renal Transplant Candidates and Recipients - Peter N. Bretan (The Scientific World Journal)
There are more than 200,000 end stage renal disease (ESRD) patients who are potential transplant candidates and more than 100,000 previously transplanted renal recipients with functioning allografts in the United States 1. Fifty-seven percent of these patients are male and forty percent are greater than 50 years of age 2, 3. Diabetes is the most common cause of kidney failure. It is evident that many patients are at high risk for development of urologic problems and thus it is estimated that the average urologist will care for up to ten of these patients yearly4. Thus a review of the genitourinary (GU) evaluation and management of these patients is timely.